Hubungan Mekanisme Koping dengan Tingkat Kecemasan Lansia pada Masa Pandemi Covid-19 di Wilayah Kerja Puskesmas Rejosari Pekanbaru - Abdurrahman Hamid; Arlina Waruwu; Awaliyah Ulfah Ayudytha Ezdha (HEALTH CARE : JURNAL KESEHATAN, 2021)
ABSTRACT Corona Virus Disease (Covid-19) is an infectious disease that can be transmitted from someone positive for Covid-19 through splashing fluids from the mouth or nose when coughing and sneezing. This Covid-19 has caused anxiety among the people of the Pekanbaru Rejosari Public Health Center, especially the elderly who are very vulnerable to the transmission of this disease. Anxiety is an intense, excessive, and persistent worry and fear about everyday situations. Things can happen such as fast heartbeats, shortness of breath, sweating, and feeling tired. The basic assumption of this research is that elderly people who have good coping mechanisms against the spread of the covid-19 virus can reduce their anxiety about the transmission of the covid-19 virus disease. This study aims to see whether there is a relationship between coping mechanisms and the level of anxiety in the elderly in the working area of the Rejosari Public Health Center Pekanbaru. The number of respondents in this study was 45 respondents. Data analysis using SPSS. It was found that the elderly's coping mechanism was in the adaptive category with 36 (80.0%). While the level of anxiety in the elderly is in mild anxiety 29 respondents (64.4%) This research is a quantitative study using a descriptive correlation research design. This study uses a Cross-Sectional Study design. Based on the results of the chi-square test, the p-value of the coping mechanism = 0.035 is smaller than the alpha value (p < 0.050), which indicates a significant relationship between Coping Mechanisms and Anxiety Levels.